Evaluation of protective immune response against fowl typhoid in chickens vaccinated with the attenuated strain Salmonella Gallinarum ΔcobSΔcbiA - Penha Filho, Rafael Antonio Casarin [UNESP]; Diaz, Silvia Juliana Acelas [UNESP]; Medina, Tiago da Silva; Chang, Yung-Fu; da Silva, João Santana; Berchieri, Angelo [UNESP] (Elsevier, 2016)
Salmonella enterica serovar Gallinarum biovar Gallinarum (SG) causes fowl typhoid in chickens, a septicemic infection which results in high mortality rates. This disease causes high economic impact to the poultry industry worldwide because of the mortality or elimination of positive flocks to control bacterial dissemination. Live vaccines are used in the fields, however the characterization of immune mechanisms important for protection are being studied to improve the efficacy of vaccination schemes. In this study, we evaluated the immune response in brown layer-hens, vaccinated or not, during the most critical period of infection. Cellular and humoral immunity were extensively evaluated until 7 days post-infection (DPI), by flow cytometry and ELISA, respectively. Furthermore, we evaluated the expression of important pro-inflammatory cytokines after infection of bone marrow derived macrophages (BMDMs) with the live attenuated SG vaccine and with the wild SG strain. The results showed an increasing production of IgG and IgM during the first week post-infection, in vaccinated layer-hens, which was absent in unvaccinated birds. The population of CD8+CD44+ and CD4+CD44+ T cells in spleen and cecal tonsils constantly decreased in unvaccinated birds in comparison with vaccinated layers. The expression of IFN-γ and TNF-α in BMDMs was induced by both SG strains (attenuated and wild) at similar levels (p>0.05). Vaccination with live SG vaccine reduced systemic infection by challenge strain of SG and prevented the mortality rate of 85% that occurred in unvaccinated layer-hens during 30 dpi. Furthermore, the immunization enhanced the proliferation of effector CD4+ and CD8+ T cells after challenge.
Keywords: Acquired immunity; BMDM; Flow cytometry; Live vaccine; T cells